TANGGUNG JAWAB NOTARIS TERHADAP PEMBUATAN PERIKATAN JUAL BELI YANG TERINDIKASI WANPRESTASI DAN AKIBAT HUKUMNYA - SELLY SELLY (PREMISE LAW JURNAL, 2016)
A Notary is a public official who has the authority to draw up authentic deeds and the other authorities as it is stipulated in Law No. 2/2014 on Notarial Position. Notary, in undertaking his job, enters into a agreement which bounds him with the stakeholders that causes legal relation so that each party is legally protected and the goal can be achieved as what has been agreed. The research was descriptive analytic. A Notary’s responsibility in drawing up a sales contract which is indicated as default is in the civil case. The process of settling it is also impeded probably because of the weakness of the regulations, these have made it difficult to settle the case of Notary X. The sanction imposed upon a Notary in drawing up a sales contract which indicated as default is civil sanction such as compensation for the cost, indemnity, and interest. Keywords: Responsibility, Sales Contract, Sanction